Utilization of Soybeans as Bio-Catalyst in Calcite Precipitation Method for Repairing Cracks in Concrete - Rahmawan, Rama Zaky; Fauzan, Muhammad; Putra, Heriansyah (Jurnal Teknik Sipil dan Perencanaan, 2021)
Concrete is a material that has high compressive strength. However, concrete has a lower tensile strength than its compressive strength. As a result, the concrete often cracks and allows the entry of harmful substances such as  dan   causing corrosion of the reinforcement. Therefore, the repair method began to shift from the conventional way to the concept of self-healing concrete which involves the deposition of CaCO3. Precipitation can be done by the enzymatically – induced carbonate precipitation (EICP) method through a combination of urease, urea, and CaCl2 into a solution. This research used soybean extract as a substitute for pure urease enzyme. Variations in the concentration of soybean flour used as injection solution were variations in the content of soybean flour 15 g/L because it produced an optimum calcite mass of 2.62 grams. As a result, there was an increase in the compressive strength of BI against BR. In addition, there was a decreased value of permeability and porosity and the number of injections carried out. The increase in compressive strength, decrease in permeability, and decrease in porosity in concrete is due to CaCO3 deposition in the concrete which can cover the pores and cracks in the concrete.